Total nucleated cell count and CD34+ cell is reduced in preeclampsia and gestational diabetes mellitus pregnancies: viable affix criteria for cord blood banking - Mohd Razif Mohd Idris; Fazlina Nordin; Zaleha Abdullah Mahdy; S. Fadilah Abd. Wahid (Penerbit Universiti Kebangsaan Malaysia, 2018)
The aim of this study to determine the numbers of CD34+ cells and total nucleated cell (TNC) in umbilical cord blood (UCB) collected from pregnant mothers with gestational diabetes mellitus (GDM) and preeclampsia (PE), following statistical analysis of both maternal and perinatal factors which affect UCB parameters. Most of studies explored the influence of obstetric factors on the number of UCB cell collection and only a few looked at the effects on UCB haematopoietic stem cell (UCB-HSC) of common disorders complicating pregnancy. A total of 112 UCB samples (32 PE, 42 GDM and 38 non-diseased) were collected. CD34+ cell and NC count were enumerated using FACS Calibur. The TNC and CD34+ cells were significantly reduced in both PE and GDM groups as compared to the control group. The PE group shows significantly lower birth weight and higher BP which led to a lower UCB volume and CD34+ count. Gestational age shows significant correlation with nucleated cell count (NCC) and TNC. GDM group shows significantly lower systolic BP, NCC and TNC count, including low placental weight and birth weight. Conclusively, some obstetrics factors have significant influences to the numbers and quality of UCB-HSC in both PE and GDM groups, which could guide in the selection criteria for CB banking.